Determinants of the Contextual Performance of Nursing Home Care Staff in the Yogyakarta Special Region - Aulia, Aulia; Mustikadewi, Annisa Widya; Yulianti, Kartika Dewi (Jurnal Psikologi, 2025)
Contextual performance plays a vital role in organizational effectiveness, contributing significantly to individual outcomes and overall workplace functioning. This study examines the influence of work engagement, job satisfaction, and organizational culture on the contextual performance of nursing home care staff in the Special Region of Yogyakarta. Utilizing a quantitative approach and correlational analysis, the study included 110 staff members selected through purposive sampling based on predetermined criteria. Four instruments were employed: a modified version of the Utrecht Work Engagement Scale (UWES), the Job Satisfaction Scale, the Organizational Culture Scale, and the Contextual Performance Scale. The findings, at a significance level of p = 0.000 (p < 0.01), reveal that work engagement, job satisfaction, and organizational culture significantly affect contextual performance (R = 0.658, R² = 0.433, F = 26.984). These results suggest a significant positive relationship between the examined variables and the contextual performance of nursing home staff in this region.